The corporate social responsibility is just a twist in a Möbius strip - Nazaria Solferino; Viviana Solferino (Economics: The Open-Access, Open-Assessment E-Journal, 2016)
In recent years economic agents and systems have become more and more interactive and juxtaposed, therefore the social sciences need to rely on the studies of physical sciences to analyze this complexity in the relationships. According to this point of view, the authors rely on the geometrical model of the Möbius strip used in electromagnetism, which analyzes the movements of the electrons that produce energy. They use a similar model in a Corporate Social Responsibility (CSR) context to devise a new cost-benefit model in order to take into account three positive effects on the efficiency of a socially responsible company: 1) cooperation among stakeholders in the same sector; 2) cooperation among similar stakeholders in different sectors; and 3) the stakeholders' loyalty toward the company. By applying this model to a firm's decision problem the authors find that investing in CSR activities is always convenient, depending on the number of sectors, the stakeholders' sensitivity to these investments and the decay rate to alienation. Their work suggests a new method of analysis which should be developed not only at a theoretical level, but also at an empirical level.
Keywords: L13; D21; Z1; 330; corporate social responsibility; econophysics; firm behavior